PROSPECTS OF LITHIUM EXTRACTION IN UKRAINE - MYKHAYLOV, Volodymyr; REVA, Maksym (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The paper examines the prospects for the development of lithium deposits, which are determined by the demand of modern industry for lithium and lithium raw materials. The supply of lithium is particularly acute for developed countries, for example, the EU is 100 % and the USA is 50 % supplied by imports of lithium raw materials. For Ukraine, lithium supply is an extremely urgent issue, caused by problems in the energy sector and the development of alternative electricity storage and transmission systems. Methods. The work used methods of collecting and analyzing funds, methods of comparison and analogies. Results. The authors provide statistics on lithium production in the world relative to estimated reserves. Statistical data show that the main sources of lithium raw materials in the world are confined to the brine of salt lakes in Chile and Bolivia, and smaller in volume are sources associated with pegmatites. Lithium deposits in Ukraine were discovered in the 80s–90s, they are associated with pegmatites: Shevchenkivske (Donetsk region), Kruta Balka (Zaporizhzhya region), Polokhivske and Stankuvatske (Kirovohrad region). The ore at the Shevchenkivske deposit and the ore at the Kruta Balka area are mainly represented by spodumene, which makes ore processing quite simple. These deposits are located in uncontrolled territory, which makes their development impossible. The ores of the Polokhivske deposit are composed mainly of petalite, and those of the Stankuvatske deposit are composed mainly of petalite and spodumene, which complicates the technology of ore processing. The authors noted that the Stankuvat deposit has greater investment attractiveness due to the estimated forecast resources of rubidium, cesium, tantalum, niobium, beryllium and tin. The article describes another promising lithium resource in Ukraine, this is produced water oil and gas fields (OGPW). Recently, this resource has been gaining popularity among researchers, as it has increased concentrations of lithium, rubidium, cesium, iodine, bromine and boron. Compared to brine from salt lakes, the concentrations of lithium in the OGPW are lower, but the advantage is that they do not require capital investments in their extraction. According to the currently available extraction technologies, it is believed that the optimal concentration of lithium in water should be 100 mg/L, the development of some deposits shows economic feasibility at concentrations of 20–30 mg/L. In the produced water of some oil and gas fields of Ukraine, lithium contents of up to 10–23 mg/L have been recorded, but it is impossible to give an objective assessment of this type of resource due to the lack of systematic research. This necessitates the need for a detailed study of the produced water of the oil and gas regions of Ukraine. Conclusions. In Ukraine, there are many problems with lithium production, since the deposits are poorly studied, there are also problems with their geological and economic assessment. However, among the indigenous lithium deposits in Ukraine, the Polokhiv deposit of petalite ores has the greatest investment attractiveness. Also, a promising resource for lithium raw materials is the OGPW.